Analisis Rekonstruksi Makna dan Kekuasaan dalam Pidato Rocky Gerung pada Kanal MimbarTube - Ghozali Bayu Eka Samudra; Roziana Febrianita (Journal Education Innovation (JEI), 2024)
The Job Creation Law has become a controversial topic and has given rise to various problems in society. Political and social dynamics continue to change, speeches from public figures are important because they can influence public opinion, shape perceptions, and mobilize the masses. One figure who is known for raising socio-political issues with a provocative perspective is Rocky Gerung. The aim of this research is to analyze the reconstruction of meaning and power in the context of workers' struggles in Rocky Gerung's speech which was broadcast via the MimbarTube channel " Pidato Panas Rocky Gerung Bersama Aliansi 1 Juta Buruh". This research adopts Teun A. Van Djik's Critical Discourse Analysis. This type of research uses qualitative with a critical approach. The data collection technique was carried out by storing and collecting data related to Rocky Gerung's heated speech with the alliance of 1 million workers. The research results show that Rocky Gerung's speech was delivered in simple language and strong rhetoric in the context of workers' dissatisfaction with the Omnibus Law policy and a government that did not side with the interests of the people, but instead colluded with capitalist forces. Rocky Gerung uses his intellectual authority to reconstruct the meaning of workers' struggle as something legitimate and necessary in the face of injustice achieved through collective action